Livestock Marketing Practices in Hassan District of Karnataka - Handage, Sushant; Manjunath, L.; Gowda, C.T. Chandre; Kumar, G.S. Naveen; Amith, N,G; Shruthi, J.S. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The present study was conducted in selected shandies of Hassan district to analyze the trading practices of the farmers with respect to livestock. About 200 participants i.e., 90 sellers, 90 buyers and 20 intermediaries were included in the study. Results revealed that livestock trading was negotiable business. About 45 percent of the farmers visited 3 to 4 shandies in a week. Livestock business was more active in the morning hours of the day. About 43 percent of the famrmers sold the animals due to distress. It was found that 54.5 percent of the farmers revealed that animals were transported through walk. Among the respondents 54.44 percent of buyers and 62.22 percent of sellers were dependent on the middlemen. Further 55 percent of the middlemen were marginal and 35 percent were landless. Most of the participants in the shandies were landless to marginal farmers. Livestock business was also a source of livelihood to many of the farmers and middlemen. The sales were completely unorganized without any weighing facility for the small ruminants.